Eastern Partnership: The Role and Significance in the Process of Transformation of the Countries of Eastern Europe and the South Caucasus (Wydawnictwo Księgarnia Akademicka, 2021)
The publication contains a collection of articles devoted to the most important aspects related to the process of transformation of the countries of Central and Eastern Europe and the South Caucasus under the Eastern Partnership program. The book covers the results of a research project by an international team of scientists who present their findings on the policy of European integration, the role and importance of the Eastern Partnership in the process of change, and give recommendations for its implementation and activities in the future.